Видатні організатори академічної науки - Пирожков, С.І.; Дубровіна, Л.А. (Вісник НАН України, 2018)
Упродовж усіх ста років існування Національної академії наук України її
очолювали видатні вчені, невтомні організатори науки. У статті йдеться про діяльність президентів Академії В.І. Вернадського (1918–1921),
М.П. Василенка (1921–1922), О.І. Левицького (1922), В.І. Липського (1922–
1928), Д.К. Заболотного (1928–1929), О.О. Богомольця (1930–1946),
О.В. Палладіна (1946–1962). Розкрито їх особистий та сукупний внесок
у вітчизняну і світову науку, у становлення Академії, розвиток інтеграції
науки, освіти, культури, виробництва. During the entire hundred years of existence of the National Academy of Sciences of Ukraine, it has been headed by
prominent scholars, tireless organizers of science. The article deals with the activities of the Presidents of the Academy
V.I. Vernadsky (1918–1921), M.P. Vasilenko (1921–1922), O.I. Levytsky (1922), V.I. Lipsky (1922–1928), D.K. Zabolotnyi
(1928–1929), O.O. Bogomolets (1930–1946), O.V. Palladin (1946–1962). Their personal and aggregate contribution
to the national and world science, the formation of the Academy, the development of the integration of science, education,
culture, and production are covered.